2020
DOI: 10.1021/acs.analchem.0c00974
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Proteomic Analysis of Small GTPases in Murine Adipogenesis

Abstract: Small GTPases are essential signaling molecules for regulating glucose uptake in adipose tissues upon insulin stimulation, and this regulation maintains an appropriate range of glycemia. The involvement of small GTPases in adipogenesis, however, has not been systemically investigated. In this study, we applied a high-throughput scheduled multiple-reaction monitoring (MRM) method, along with the use of synthetic stable isotope-labeled peptides, to identify differentially expressed small GTPase proteins during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In this regard, we developed and utilized MS‐based approaches for targeted quantitative proteomic analysis of small GTPases of the Ras superfamily in cancer cells and tissues. By employing MRM, in conjunction with the use of SILAC or crude synthetic SIL peptides, we achieved high‐throughput targeted quantitative profiling of the altered expressions of small GTPases accompanied with cancer metastasis and drug resistance in cultured human cancer cells, adipocyte differentiation in murine cells, and development of neurodegenerative diseases in patient‐derived tissue samples (Huang & Wang, 2018, 2019; Huang et al, 2018, 2019; Yang, Huang, & Wang, 2020). By virtue of its superior sensitivity, reproducibility, and specificity, MRM has been widely used for targeted proteomics during the past two decades; however, owing to the use of low‐resolution mass analyzer in MS/MS analysis, the method is more susceptible to background interference from sample matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we developed and utilized MS‐based approaches for targeted quantitative proteomic analysis of small GTPases of the Ras superfamily in cancer cells and tissues. By employing MRM, in conjunction with the use of SILAC or crude synthetic SIL peptides, we achieved high‐throughput targeted quantitative profiling of the altered expressions of small GTPases accompanied with cancer metastasis and drug resistance in cultured human cancer cells, adipocyte differentiation in murine cells, and development of neurodegenerative diseases in patient‐derived tissue samples (Huang & Wang, 2018, 2019; Huang et al, 2018, 2019; Yang, Huang, & Wang, 2020). By virtue of its superior sensitivity, reproducibility, and specificity, MRM has been widely used for targeted proteomics during the past two decades; however, owing to the use of low‐resolution mass analyzer in MS/MS analysis, the method is more susceptible to background interference from sample matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the levels of RAB3A, RAB3D, and RAB27B proteins, which are involved with synaptic and secretory vesicles, were found to increase in brain tissue samples with elevated disease severity (Huang et al, 2019). More recently, the application of GeLC–MRM assay facilitated by SIL peptides was extended to investigating the differential protein expression of small GTPases during adipogenesis in cultured murine cells, where a panel of small GTPases were downregulated and Rab32 was found to play a previously unidentified role in inhibiting adipocytic differentiation (Yang, Huang, & Wang, 2020). Collectively, these studies demonstrated the robustness of the adapted GeLC–MRM quantitative proteomic workflow in high‐throughput interrogation of small GTPase proteome in cultured mammalian cells and tissues.…”
Section: Proteomic Studies Of Gtp‐binding Proteinsmentioning
confidence: 99%
“…24,25 The MRM library contained a unique peptide for each of the 144 small GTPases, which represent approximately 85% of the human small GTPase proteome. 27,37 To fulfill sensitive and reproducible quantification, we selected the three most abundant fragment ions for each peptide based on MS/MS obtained from shotgun proteomic analyses. We realized that the potential differences in efficiencies of tryptic digestion and peptide recovery from gels may affect the quantification accuracies for small GTPases.…”
Section: Mrm-based Targeted Proteomic Profiling Of Differential Expre...mentioning
confidence: 99%
“…In the present study, we test the above hypothesis by analyzing comprehensively the alterations in small GTPase proteome in HEK293T cells upon CRISPR-Cas9-mediated ablation of METTL3 , ALKBH5 , FTO , YTHDF1 , YTHDF2 , and YTHDF3 genes . To achieve quantifications of small GTPase proteins in high sensitivity, reproducibility, and throughput, we employed a previously developed scheduled multiple-reaction monitoring (MRM)-based quantitative proteomic approach, together with the use of synthetic stable isotope-labeled peptides as internal standards. We observed altered protein expression of several small GTPases, including the known tumor suppressor RHOB and metastasis driver RHOC, in cells depleted of METTL3 or ALKBH5.…”
mentioning
confidence: 99%
“…Quantitative mass spectrometry reporting the relative or absolute quantities of target peptides and proteins is very important for biological research. Although relative quantification is now routinely used to provide valuable information on alteration of protein abundance in a proteome-wide scale, the absolute quantitation determines the absolute concentration of target peptides and proteins within a sample, providing a far more precise description of molecular events in the biological processes . Moreover, absolute quantitation is crucial for the evaluation of clinical biomarker candidates and enables the data integration and comparison among different laboratories. For the MS-based absolute quantitation of peptides and proteins, the isotope-labeled internal standards and the calibration curve are often needed .…”
Section: Introductionmentioning
confidence: 99%